Synthesis of biodiesel from prosopis juliflora and using MCDM analytical hierarchy process technique for evaluating with different biodiesel. Issue 1 (1st January 2021) - Kukana, Rajendra; Jakhar, Om Prakash
Abstract: The continuous depletion of energy sources globally and serious concern regarding environmental degradation by the use of fossil fuel, biodiesel may plays key transponder. Bio diesel with diesel fuel attains a reduced environmental impact without compromising the performance and utilization efficiency. This research focus on the production of biodiesel from Prosopis Juliflora and Analytical Hierarchy Process (AHP) technique used for ranking of Prosopis Juliflora with four different biodiesel by physiochemical properties using weighted value criteria. Among the evaluated physiochemical fuel properties, the most important is Calorific Value and rank of Prosopis Juliflora is third of different biodiesel considered.